Osteoblasts induce glucose-derived ATP perturbations in chondrocytes through noncontact communication - Wei Jieya; Yang Yueyi; Guo Daimo; Xu Siqun; Huang Hongcan; Zhang Demao; Xie Jing; Zhou Xuedong (Acta Biochimica et Biophysica Sinica)
Cartilage and subchondral bone communicate with each other through material and signal exchanges. However, direct evidence provided by experimental studies on their interactions is insufficient. In the present study, we establish a noncontact co-culture model with a transwell chamber to explore the energetic perturbations in chondrocytes influenced by osteoblasts. Our results indicate that osteoblasts induce more ATP generation in chondrocytes through an energetic shift characterized by enhanced glycolysis and impaired mitochondrial tricarboxylic acid cycle. Enhanced glycolysis is shown by an increase of secreted lactate and the upregulation of glycolytic enzymes, including glucose-6-phosphate isomerase (Gpi), liver type ATP-dependent 6-phosphofructokinase (Pfkl), fructose-bisphosphate aldolase C (Aldoc), glyceraldehyde-3-phosphate dehydrogenase (Gapdh), triosephosphate isomerase (Tpi1), and phosphoglycerate kinase 1 (Pgk1). Impaired mitochondrial tricarboxylic acid cycle is characterized by the downregulation of cytoplasmic aspartate aminotransferase (Got1) and mitochondrial citrate synthase (Cs). Osteoblasts induce the activation of Akt and P38 signaling to mediate ATP perturbations in chondrocytes. This study may deepen our understanding of the maintenance of metabolic homeostasis in the bone-cartilage unit.